2012
DOI: 10.1542/peds.2011-2199
|View full text |Cite
|
Sign up to set email alerts
|

The Diet Factor in Attention-Deficit/Hyperactivity Disorder

Abstract: This article is intended to provide a comprehensive overview of the role of dietary methods for treatment of children with attention-deficit/hyperactivity disorder (ADHD) when pharmacotherapy has proven unsatisfactory or unacceptable. Results of recent research and controlled studies, based on a PubMed search, are emphasized and compared with earlier reports. The recent increase of interest in this form of therapy for ADHD, and especially in the use of omega supplements, significance of iron deficiency, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
135
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(150 citation statements)
references
References 64 publications
4
135
0
11
Order By: Relevance
“…In a Spanish case-control study, ADHD patients had lower calcium, iron, magnesium, zinc, selenium and phosphorous, thiamine, niacin, vitamin B 6 , and folate intakes than control subjects (52). Similarly, low levels of copper, iron, zinc, and iodine were associated with ADHD in a Korean study (49,51), and certain ADHD symptoms were linked to low levels of magnesium and zinc in Australian adolescents (62). Low zinc was also identified as being associated with ADHD in a case-control study of Chinese children (63).…”
Section: Grains Chos and Dietary Patternsmentioning
confidence: 91%
See 4 more Smart Citations
“…In a Spanish case-control study, ADHD patients had lower calcium, iron, magnesium, zinc, selenium and phosphorous, thiamine, niacin, vitamin B 6 , and folate intakes than control subjects (52). Similarly, low levels of copper, iron, zinc, and iodine were associated with ADHD in a Korean study (49,51), and certain ADHD symptoms were linked to low levels of magnesium and zinc in Australian adolescents (62). Low zinc was also identified as being associated with ADHD in a case-control study of Chinese children (63).…”
Section: Grains Chos and Dietary Patternsmentioning
confidence: 91%
“…Enzymatic processing still needs to be improved by, for example, decreasing the treatment time using new or current enzymes. In enzymatic treatment of wheat bran with xylanase (a cell wall-degrading enzyme) at high consistency, we showed that the proteins from the bran aleurone cells were released; however, their solubility was reduced (49). By releasing the proteins from the bran matrix, the bioavailability of the proteins can be improved.…”
Section: Fractionation and Extraction Of Proteins From Cereal Side-stmentioning
confidence: 99%
See 3 more Smart Citations